Albumin and psychological resilience: key modifiable factors for hospital length of stay in ulcerative colitis - Yang, Man; Lei, Lei; An, Huiying; Shi, Lili; He, Yingya; Yang, Meng; Peng, Lifang; Li, Liming; Ding, Xiangming; Luo, Xiaoying (Frontiers in Nutrition, 2026)
BackgroundReducing the length of stay (LOS) for patients hospitalized with inflammatory bowel disease is crucial for lowering healthcare costs and improving patients’ quality of life. However, the determinant factors of LOS in ulcerative colitis (UC) patients are incompletely understood.MethodsParticipants were obtained from the Henan Provincial People’s Hospital during the period from January 2018 to April 2025. Information on multidimensional determinants of LOS was collected using a questionnaire. Spearman correlation analysis and negative binomial regression models were performed to identify factors associated with LOS. A subgroup analysis was performed to examine the disease stage and severity in relation to LOS. The interaction of identifying factors was analyzed.ResultsA total of 400 active UC-related hospitalizations were identified. Correlation analysis showed that LOS was positively correlated with mMayo score, improved Mayo endoscopic score, white blood cell count, platelet, C-reactive protein, and gamma-glutamyl transferase levels. However, LOS was negatively correlated with red blood cell count, hemoglobin, albumin, and total cholesterol levels. A negative binomial regression model showed that albumin reduction was associated with prolonged LOS in active UC patients, regardless of disease severity. Decreases in albumin level and Connor–Davidson Resilience Scale score were associated with increased LOS, and their corresponding estimated incidence rate ratios and 95% confidence intervals were 0.967 (0.937, 0.997) and 0.434 (0.188, 1.003), respectively. An interaction of these variables on LOS was observed in the remission stage of patients.ConclusionThis study found that lower serum albumin levels were significantly associated with a longer LOS in patients with active UC. Furthermore, both lower albumin levels and poorer psychological resilience were associated with prolonged LOS. This study’s findings suggest that albumin optimization may be an effective strategy for reducing LOS in active UC, and further integrating psychological resilience–building interventions into standard care could help shorten hospitalization and improve outcomes for patients in remission.